On g-functions for subshifts - Krieger, Wolfgang (Dynamics & stochastics, 2007)
A necessary and sufficient condition is given for a subshift presentation to have a continuous g-function. An invariant necessary and sufficient condition is formulated for a subshift to posses a presentation that has a continuous g-function.
First available in Project Euclid: 28 November 2007
Gesehen am 06.08.2018